Integration of Natural and Artificial Light on Energy Efficiency of the Mega Bank Makassar Tower Building - Isty Cahyani Ismail; Ramli Rahim; Baharuddin Hamzah (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2021)
One of the largest energy consumers in the world is buildings. The energy consumption comes from the lighting system. Energy use in buildings is generally 25% for lighting systems. The strategy used in building design is to reduce energy consumption while maintaining the best comfort in a building. The application of energy-saving concepts from the building sector is optimizing the lighting system by integrating natural and artificial lighting systems. This study aims to determine the light intensity in the integrated lighting system of natural and artificial manually and also to find out how much energy can be saved with the integrated lighting system manually. The research location is at the Mega Bank Makassar Tower Building. The research sample was selected by purposive sampling and the sixth floor was chosen as the research location. In this study, simulations were carried out using the DIAlux 4.13 program to integrate natural and artificial light and to calculate the amount of energy efficiency in the workspace. To obtain optimal light intensity and energy savings, a simulation was carried out by turning off half the light points in the workspace, especially the light points around the building openings. The simulation results show that the average integrated lighting quality meets the minimum lighting requirements and can save energy usage by up to 50%. Keywords: energy efficiency; integration lighting; workspace